Expression of a Bifunctional Chimeric Protein A-Vargula hilgendorfii Luciferase in Mammalian Cells. (January 1996) - Maeda, Y.; Ueda, H.; Hara, T.; Kazami, J.; Kawano, G.; Suzuki, E.; Nagamune, T.
We have designed and constructed a novel chimeric protein that consisted of a single domain of protein A and luciferase derived from sea-firefly Vargula hilgendorfii with the goal of obtaining a heterofunctional immunological tool. The structural gene of luciferase was fused to the 3′ terminus of the D domain gene of protein A with/without a short linker of five amino acids. The resulting constructs under the transcriptional regulation of the Rous sarcoma virus (RSV) promoter, were expressed transiently in simian COS-1 and stably in Chinese hamster ovary (CHO) cells. The properties of the resultant chimeric protein were characterized. The results indicated that the dual properties of the chimeric protein could be retained only after the introduction of a linker of (Gly)4 Ser between the two conjugated moieties. Moreover, the chimeric protein was found to retain at least 50% of the specific activity as compared with the non-fused luciferase. The future prospect of the usage of this chimeric protein in the field of diagnostics was further evaluated by performing bioluminescent immunoassays.